Automated testing in Microsoft Dynamics 365 Business Central : efficiently automate test cases in Dynamics Nav and Business Central - Vugt, Luc van (Packt Publishing, Limited, 2019)
Dynamics 365 Business Central is the new Cloud-based SaaS ERP proposition from Microsoft. It's not as simple as it used to be way back when it was called Navigator, Navision Financials, or Microsoft Business Solutions-Navision. Our development practices are becoming more formal, and with this the call for test automation is pressing on us. ...